On the design of a Human-in-the-Loop Cyber-Physical System for online monitoring and active mitigation of indoor Radon gas concentration - Lopes, Sérgio I. (2020)
This paper presents the design methodology used to specify a Human-in-the-Loop Cyber-Physical System (HITLCPS)for online monitoring and active mitigation of the indoor radon gas concentration in non-residential granitic buildings with regular human occupation restricted to a work schedule, such as public buildings like administration offices, schools, kindergartens, etc. The paper follows the methodology that is being carried out in the RnMonitor R&D project in order to design the overall CPS architecture specification using the following approach: i) Conceptual Approach and Application Requirements; ii) Design Specifications and iii) Architecture Definition. At the end, main conclusions are presented alongside with a set of promising avenues for future development.